Colonos e colonizadores no oeste de Santa Catarina: a atuação da companhia territorial sul Brasil na seção Anta Gorda (1930-1960) - Rodrigues, Márcio Luiz (2016)
This work has to analyze the participation of the Territorial Company South Brazil, the process colonization in the region west of Santa Catarina, in the decades from 1930 to 1960. Initially, Santa Catarina west region was occupied by indigenous people and mestizos, and the beginning of the process new individuals colonization, from the 1920, new individuals migrate to region, mainly descendants of Italian and German, welcome to your big most of Rio Grande South, migrated to the region, stimulated by colonizing companies, located, also mostly in the same State. It is understood the constitution of Territor its colonization project Company South Brazil, and marketing methods lots and woods. The company, formed by a group of investors, had its headquarters in Rio Grande do Sul and taking advantage offered by the government Santa Catarina, formed an extensive colonial complex with more than 48 sessions: system adopted for homogenizing by rural and secondary roads, colonization and local systematize the sale of lots, resulting in the emergence "community centers" or "lines". It is in this scenario, the dissertation sought show one 48 sessions administered the Territorial Company South Brazil: Section Anta Gorda, located east of the area acquired by the company, which has an approximate length of 16.236.00 km², being subdivided, thereafter, I section II section. Area currently consists the municipalities of Santa Catarina Modelo, Pinhalzinho and Saudades. Methodologically, the dissertation is it guided in the proposal micro-history, seeking reduction of scale observation and environmental history, proposing to highlight the mutual influences of natural features, in their colonization process. The sources used in the dissertation are basically documents produced by the colonizing company, located in the documentary collection of the Municipal Museum Father Fernando Nagel in the city of Maravilha-SC; photographs and testimonials, located in Pinhalzinho History Museum in the city of Pinhalzinho-SC and the Municipal Museum Elmiro Wagner, located in Palmitos-SC; More periodicals Journal of the Chapecó Voice, located in the documentary collection in Western Memory Center of Santa Catarina CEOM / UNOCHPECÓ in Chapecó-SC.